Factors affecting the stability of chitosan/tripolyphosphate micro- and nanogels: resolving the opposing findings1. Issue 29 (7th August 2015) - Huang, Yan; Cai, Yuhang; Lapitsky, Yakov
<x xml:space="preserve">Abstract</x> The stability of submicron chitosan/tripolyphosphate particles depends on the chitosan type, pH, ionic strength and particle concentration.